(3GdahGFO GddWjaI hGdaQGFO GdTQjaIs - (3MajO SYO GdOjf GdJaJGRGfis; (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s ((3GdLGeY GdCRgQ (B_ (3GdbGgQI s)
(3ChdgG (B:s
(3bhdg (B: (3fMeOc , EfeG ENJGQ GdMeO Ydi GdTcQ , eY Cf GdMb HGOQ ef GdYHGQI Cf GdeMehO Ydjg gfG fYeI TQM GdUOQ hJfhjQ GdbdH , hbO bGd Gddg JYGdi (B( (3dFf TcQJe dCRjOfce (B) (3dCf OjHGLI GdbQBf GdeLjO ehTMI HbQI GdJMejO s
(3BNQgG (B:s
(3bhdg (B: (3hbhakG HgG UMHi EdN hbhakG fUH Ydi GdMGd , hGdYGde ajgG ai GdHjJ GdSGHb , cCfg bGd (B: (3bafG fHc MGd hbha CUMGHi hEScGfge Ydi eWjJge hbGd LGeYI gPG BNQ eG bUOfG EHQGOg ef GdahGFO GddWjaI hGHJNQLJ cKjQkG efgG HbQjMJi hacQs
(3GdfSNI HgG MhGTs
(3YHGQg Yf ahGFO haQGFO CNPgG eDdagG ef eTGgjQ GdCFeI GdCYdGe heJCNQi GdCs
(3fSNI eUMMIs
(3YdjgG MhGTi s
(3hHgG fXGe GdJYbjHI s
(3cJHJ HYV YHGQGJgG HGdMeQI s
Keywords: (3GdadSaI hGdefWbs